Answer: (x, y)=(0, -6)
Explanation:
To solve a system of equations there are usually 3 general ways.
- Elimination
- Substitution
- Augmented Matrix
Since the question is asked to use elimination, we are going to use it.
--------------------------------------------------------------------------------------
-5x+4y=30
2x+3y=-12
-10x+8y=60
10x+15y=-60
23y=0
y=0
------------------------------------------------------------------------------------------
Substitute the y value into any one of the equations
2x+3y=-12
2x+3(0)=-12
2x+0=-12
x=-6
Hope this helps!! :)
Please let me know if you have any questions